2018
DOI: 10.1155/2018/2031571
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen-A, B, C, DRB1, and DQB1 Allele and Haplotype Frequencies in a Subset of 237 Donors in the South African Bone Marrow Registry

Abstract: Human leukocyte antigen- (HLA-) A, HLA-B, HLA-C, HLA-DRB1, and HLA-DQB1 allele and haplotype frequencies were studied in a subset of 237 volunteer bone marrow donors registered at the South African Bone Marrow Registry (SABMR). Hapl-o-Mat software was used to compute allele and haplotype frequencies from individuals typed at various resolutions, with some alleles in multiple allele code (MAC) format. Four hundred and thirty-eight HLA-A, 235 HLA-B, 234 HLA-DRB1, 41 HLA-DQB1, and 29 HLA-C alleles are reported. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 62 publications
8
12
1
Order By: Relevance
“…The common HLA types identified in this study population were compared with common HLA types found in populations of different nationalities (Table 2). [31][32][33][34][35] Common HLA frequencies at the A allele in our study corresponded to those found in a British, French, Chinese, and African American population. [31][32][33][34][35] B and DRB1 loci, common in British and French populations, were also well represented in our population.…”
Section: Resultssupporting
confidence: 88%
“…The common HLA types identified in this study population were compared with common HLA types found in populations of different nationalities (Table 2). [31][32][33][34][35] Common HLA frequencies at the A allele in our study corresponded to those found in a British, French, Chinese, and African American population. [31][32][33][34][35] B and DRB1 loci, common in British and French populations, were also well represented in our population.…”
Section: Resultssupporting
confidence: 88%
“…All HLA allele group subsets deviated from the expected HWE (p < 0.05), even within the different reported ethnic groups. This finding was expected based on our population's diverse heterogenous genetic makeup and is comparable to results reported from similarly diverse populations [ 13 , 21 ]. We determined the three most common allele groups for each subtype for the total population, the various ethnic groups, and the donor populations ( Table 2 ).…”
Section: Resultssupporting
confidence: 92%
“…Therefore, targeted HLA sequencing of the diverse southern African populations is essential to increase their representation in global reference panels [ 12 ]. According to a 2018 South African Bone Marrow Registry (SABMR) study, determining HLA alleles and haplotypes will contribute to the development of a resource for disease association, anthropology, and evolutionary studies, support models for population-specific vaccine development and advance donor enrolment in South African populations [ 13 ]. The last formal study on people residing in our local Free State Province, South Africa, was published in 1997 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent alleles were HLA-A∗23:01 (31.4%), HLA-C∗07:01 (29.3%) and HLA-C∗04:01 (28.6%). These common HLA types have been previously described in other populations in sub Saharan Africa (SSA), and in Cameroon, HLA-A∗23:01, HLA-C∗04:01 and HLA-C∗07, have been reported to be very common ( Ellis et al., 2000 ; Shepherd et al., 2015 ; Spinola et al., 2008 ; Torimiro et al., 2006 ; Tshabalala et al., 2018 ; Yindom et al., 2010 ). In the present study, the number of individuals carrying either HLA-A∗30:01 or HLA-C∗17:01 was significantly higher in the groups infected with either HBV or HCV, respectively, suggesting that these alleles may predispose their carriers to acquiring these hepatitis viruses.…”
Section: Discussionsupporting
confidence: 54%